The setting up of a Virtual Reality Lab: The Unisel experience - Rahayu, Abdul Rashid; Yusliza, Yussof; Arazi, Idrus, Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/